Determinants of Passengers’ Satisfaction in Public Transport in Tanzania: A Mediating Effect of Efficiency of Public Transport Services - Shatta, Deus; Myamba, Benitha (Journal of Industrial Engineering & Management Research, 2024)
Few studies in the current literature have, however, systematically examined the underlying relationships among service attributes to assess their influence on passenger overall satisfaction. This study assessed the determinants of passengers’ satisfaction in Tanzania. The study was guided by SERVQUAL Model. Positivism research paradigm and simple random sampling technique were used to obtain a sample size of 384 respondents. However, descriptive and explanatory cross-sectional survey research approaches were employed in data collection. Data were collected through questionnaire and documentary review. Inferential statistics analysis for the collected data was conducted using Partial Least Squares Structural Equation Modeling assisted by SmartPLS 4 software and for descriptive statistics analysis, IBM SPSS Statistics Version 26 was used for data collected regarding respondents’ profile. The findings reveal that accessibility, affordability, reliability and efficiency of public transport services have positive effects on passengers’ satisfaction. The study recommends that transport operators in Tanzania and other developing countries should consider the accessibility, affordability, reliability and efficiency of public transport services in order to satisfy the passengers who always use public transport.